Preparation method, product and application of polyaniline modified composite membrane

By coating SiO2, polyaniline and polyvinylpyrrolidone on the surface of the polyvinylidene fluoride film, a polyaniline modified composite film was prepared, which solved the problems of poor oil-water separation and poor environmental protection in the prior art, and achieved efficient and environmentally friendly oil-water separation effect.

CN119819144AActive Publication Date: 2025-04-15CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510163475.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-15
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

Existing oil-water separation technologies are not effective in the separation of transformer oil-water mixtures, and may produce by-products or emissions that are harmful to the environment, and it is difficult to maintain their separation performance for a long time.

Method used

The polyaniline modified composite film is prepared by surface coating using polyvinylidene fluoride film as the substrate. The separation efficiency and environmental protection of the film are improved by combining materials such as SiO2, polyaniline and polyvinylpyrrolidone.

Benefits of technology

It achieves efficient oil-water separation, with membrane flux up to 458.48Lm-2h-1, separation efficiency up to 98.73%, and has good pollution resistance and reusability, effectively reducing the harm of industrial wastewater to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819144A_ABST
    Figure CN119819144A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a preparation method, a product and application of a polyaniline modified composite membrane. The preparation method of the polyaniline modified composite membrane comprises the following steps: step 1, activating and cleaning a polyvinylidene fluoride base sheet, then soaking the polyvinylidene fluoride base sheet in a solution A, stirring, taking out the polyvinylidene fluoride base sheet after stirring, and cleaning the polyvinylidene fluoride base sheet to obtain the treated polyvinylidene fluoride base sheet; 2, mixing the solution A and the solution B, and filtering to obtain a mixed solution; and step 3, soaking the treated polyvinylidene fluoride base sheet in the mixed solution, taking out the polyvinylidene fluoride base sheet after soaking is finished, and drying the polyvinylidene fluoride base sheet to obtain the polyaniline modified composite membrane. The solution A is a SiO2 solution; the solution B is a mixed solution of polyaniline and polyvinylpyrrolidone. The preparation method is simple and easy to operate, industrial production is facilitated, and the polyaniline modified composite membrane is high in floating oil / water solution separation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation method, product and application of a polyaniline modified composite film. Background Art

[0002] Mineral insulating oil is widely used in large power equipment such as transformers and reactors due to its excellent insulation and heat dissipation properties. In order to prevent pollution caused by oil spraying and oil leakage from large oil-filled electrical equipment such as main transformers and high-voltage reactors, a special accident oil pool is set up in the substation. While storing the oil leakage of power equipment and the sewage of the substation, the accident oil pool also increases the safety hazards of the substation and a series of sewage leakage environmental protection problems. Transformer waste oil contains a variety of toxic components, such as polycyclic aromatic hydrocarbons, biphenyls and heavy metals. If these transformer waste oils are not treated thoroughly and in a timely manner, they will threaten the health of animals, plants and humans. Therefore, it has become an important issue facing the current management of waste liquid in the accident oil pool of substations to adopt scientific and efficient oil-water separation methods, strengthen the treatment of oily sewage at the sewage outlet of the accident oil pool, and make the waste liquid discharge meet the requirements of economic and environmental protection.

[0003] As a conductive polymer, polyaniline has good redox reversibility, conductivity and stability, and has potential advantages for oil-water separation. The current oil-water separation technology is only applicable to specific types of oil-water mixtures, and has poor separation effect on transformer oil-water mixtures. At the same time, it may produce some byproducts or emissions that are harmful to the environment and it is difficult to maintain its separation performance for a long time. Therefore, when developing new oil-water separation technologies, how to enhance the adaptability, environmental protection and sustainability of the membrane is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing a polyaniline modified composite membrane, a product and an application thereof; the method of the present invention adopts a surface coating method to prepare a polyaniline modified composite membrane with high separation efficiency, good water flux and long service life using a polyvinylidene fluoride membrane as a substrate.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a method for preparing a polyaniline modified composite membrane, comprising the following steps:

[0007] Step 1, activating and cleaning the polyvinylidene fluoride sheet, and then immersing it in solution A and stirring it. After the stirring is completed, the polyvinylidene fluoride sheet is taken out and cleaned to obtain a treated polyvinylidene fluoride sheet;

[0008] Step 2, mixing the solution A and the solution B and filtering them to obtain a mixed solution;

[0009] Step 3, soaking the treated polyvinylidene fluoride sheet in the mixed solution, taking it out and drying it after soaking, to obtain the polyaniline modified composite film;

[0010] The solution A is SiO 2 Solution;

[0011] The solution B is a mixed solution of polyaniline and polyvinyl pyrrolidone.

[0012] The second technical solution of the present invention is a polyaniline modified composite membrane prepared according to the above-mentioned preparation method.

[0013] The third technical solution of the present invention is the application of the above-mentioned polyaniline modified composite membrane in oil-water separation.

[0014] The present invention discloses the following technical effects:

[0015] The polyaniline modified composite membrane provided by the present invention has high membrane flux, good antifouling and reusability. 2 , polyaniline and polyvinyl pyrrolidone as the main materials, achieving a high floating oil separation efficiency, and has good anti-fouling and reusability, effectively reducing the harm of industrial wastewater to the environment, and has good environmental protection.

[0016] The membrane flux of the polyaniline modified composite membrane of the present invention is as high as 458.48Lm -2 h -1 The separation efficiency is as high as 98.73%. After multiple cycle tests, the total organic carbon content of the filtrate was detected to be 17.2 mg / L, which meets the national wastewater discharge standards.

[0017] The preparation method of the invention is simple and easy to operate and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is an optical photograph of the PANI@PVDF-3 composite film prepared in Example 3 of the present invention.

[0020] Figure 2 FESEM images of PVDF membrane (a) and PANI@PVDF-3 composite membrane (b, c) prepared in Example 3 of the present invention.

[0021] Figure 3 AFM images of PVDF membrane (a, b) and PANI@PVDF-3 composite membrane (c, d).

[0022] Figure 4 The oil-water separation device used in the oil-water separation cycle test of the present invention.

[0023] Figure 5 Graph showing the test results of separating floating oil / water solution using five kinds of PANI@PVDF composite membranes prepared in Examples 1 to 5 of the present invention.

[0024] Figure 6 This is a characterization diagram of the membrane flux and total organic carbon content (TOC) of the PANI@PVDF-3 composite membrane prepared in Example 3 of the present invention during recycling. DETAILED DESCRIPTION

[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0026] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0030] The first aspect of the present invention provides a method for preparing a polyaniline modified composite membrane, comprising the following steps:

[0031] Step 1, activating and cleaning the polyvinylidene fluoride sheet, and then immersing it in solution A and stirring it. After the stirring is completed, the polyvinylidene fluoride sheet is taken out and cleaned to obtain a treated polyvinylidene fluoride sheet;

[0032] Step 2, mixing the solution A and the solution B and filtering them to obtain a mixed solution;

[0033] Step 3, soaking the treated polyvinylidene fluoride sheet in the mixed solution, taking it out and drying it after soaking, to obtain the polyaniline modified composite film;

[0034] The solution A is SiO 2 Solution;

[0035] The solution B is a mixed solution of polyaniline and polyvinyl pyrrolidone.

[0036] In some embodiments of the present invention, the polyvinylidene fluoride sheet is placed in anhydrous ethanol for activation; the activation time is 0.5 to 3 hours.

[0037] The activation process can be left to stand; the main purpose of activating the membrane with anhydrous ethanol is to remove residual solvents and impurities on the membrane surface, clean the pores, improve the pore structure of the membrane, and enhance the permeability, thereby improving the permeability and hydrophilicity of the membrane. In addition, the activation treatment helps to reduce the blockage of the membrane pores, promote the uniform penetration of the liquid, and enhance the stability of the membrane and subsequent performance. Through activation, the pore channels of the membrane are optimized, laying a better foundation for oil-water separation or filtration processes.

[0038] In some embodiments of the present invention, the SiO 2 The concentration of the solution A is 2 to 10 g / L; the solvent of the solution A is dimethylformamide; the SiO 2 The particle size is 5nm~50nm.

[0039] SiO in solution A 2 The concentration has an important influence on the performance of polyaniline modified composite membranes. 2 Too high a concentration will reduce the membrane porosity, flux, and make the membrane fragile and easy to break; too low a concentration will make the membrane mechanically weak and reduce the separation efficiency, especially when treating wastewater with high oil concentration. 2 The concentration should be kept within an appropriate range (2-10 g / L) to ensure membrane stability and good separation performance.

[0040] At the same time, SiO 2Particle size also plays a crucial role in the performance of the membrane. SiO 2 When the particle size is too large, the pore structure of the membrane is too coarse, the separation accuracy is reduced, the separation effect is poor, and the membrane surface is rough and easy to accumulate contamination; SiO 2 If the particle size is too small, the pores of the membrane will be too fine, the flux will be reduced, the treatment efficiency will be weakened, and it will be more susceptible to contamination and clogging. 2 The particle size should be controlled between 5nm and 50nm to balance the flux, separation efficiency and membrane stability.

[0041] In some embodiments of the present invention, the solution A is prepared by mixing SiO 2 The powder is dispersed in dimethylformamide and stirred for 1 to 3 hours.

[0042] Dimethylformamide is a polar solvent. 2 It has good dispersibility, helps to form a uniform dispersion system, improves its fluidity and formability in subsequent processing, and reduces the difficulty of preparing films.

[0043] If other polar solvents such as ethyl acetate, ethanol, acetone, tetrahydrofuran or dimethyl sulfoxide are used to replace dimethylformamide (DMF), the performance of the polyaniline modified composite membrane will be adversely affected. First, the dispersibility of ethyl acetate and ethanol is poor, resulting in the formation of SiO 2 The particles are unevenly dispersed, which in turn affects the uniformity and mechanical strength of the film. Although acetone has strong solubility, it is not suitable for dispersing SiO 2 , and the volatilization speed is fast, which affects the film forming property and surface smoothness. Tetrahydrofuran (THF) can disperse SiO 2 , but it interacts with polyaniline, affecting the electrical properties and mechanical strength of the membrane. In addition, THF is volatile, resulting in uneven membrane formation. Dimethyl sulfoxide (DMSO) has strong dispersibility, but its polarity is high, affecting the hydrophilicity of the membrane, reducing the oil-water separation effect, and having an adverse effect on polyaniline.

[0044] In summary, although these solvents are effective in dispersing SiO 2 have some ability, but compared with dimethylformamide, they will lead to SiO 2 Uneven dispersion, difficult film forming, poor film stability and influence on polyaniline. Therefore, dimethylformamide is a more suitable choice.

[0045] In some embodiments of the present invention, the concentration of polyaniline in the solution B is 5 to 15 g / L, specifically, 5 g / L, 10 g / L, and 15 g / L; the concentration of polyvinyl pyrrolidone in the solution B is 2 to 10 g / L, specifically, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 8 g / L, and 10 g / L; the solvent of the solution B is 0.5 to 1.5 mol·L -1 of hydrochloric acid solution.

[0046] In some embodiments of the present invention, polyaniline (PANI) and polyvinyl pyrrolidone are dissolved in a solution having a concentration of 1 mol·L -1 In an acidic environment, the amino group (-NH) of polyaniline reacts with hydrogen ions (H + ) combination, PANI+HCl→PANI + +Cl - , thereby forming protonated polyaniline and increasing its solubility in acidic environments. At the same time, polyvinyl pyrrolidone, as a water-soluble polymer, can form a complex or blend with polyaniline to improve its dispersibility and uniformity. This blending can enhance the conductivity and mechanical properties of the polyaniline-modified composite membrane, while improving the physical and chemical stability of the polyaniline-modified composite membrane.

[0047] If the concentrations of polyaniline (PANI) and polyvinyl pyrrolidone (PVP) in solution B exceed the parameter ranges recorded above, the properties of the composite membrane will be adversely affected, as follows:

[0048] Too high a polyaniline concentration will increase the brittleness of the membrane, reduce the mechanical strength of the membrane, and easily cause cracks or ruptures. In addition, too high a polyaniline concentration will make the membrane too conductive, affecting its application performance and causing a decrease in the flux of the membrane. On the contrary, too low a polyaniline concentration will make the electrical properties of the membrane insufficient, the mechanical strength of the membrane weak, and affect the stability of the membrane.

[0049] A high concentration of polyvinyl pyrrolidone may increase the swelling of the membrane, affect the stability and structure of the membrane, increase the surface roughness, and reduce the separation effect of the membrane. A low concentration may lead to poor stability and insufficient hydrophilicity of the membrane, affecting the wettability and separation performance of the membrane, especially in applications such as water treatment.

[0050] In some embodiments of the present invention, in step 1, the stirring parameters are set to: stirring at a temperature of 35 to 75° C. and a speed of 400 to 600 r / min for 1 to 3 hours.

[0051] The stirring parameters in step 1 (such as stirring speed and time) are critical to ensuring the uniformity of the solution and the performance of the membrane.

[0052] If the stirring speed is too high, bubbles will be introduced, affecting the surface quality of the membrane, and the high shear force will cause uneven dispersion of particles, thus affecting the mechanical and electrical properties of the membrane. On the contrary, if the stirring speed is too low, the particles cannot be fully dispersed, resulting in uneven components in the solution, affecting the stability of the membrane and the separation effect.

[0053] If the stirring time is too long, the solution temperature will rise, affecting the formability of the film, and even causing the degradation or over-polymerization of the material. If the stirring time is too short, the solution will not be fully mixed, the dispersion of polyaniline and PVP will be uneven, and the mechanical strength and performance of the film will be affected.

[0054] Therefore, the stirring speed and time should be controlled within an appropriate range to ensure the uniformity of the solution and avoid adverse effects on the performance of the membrane.

[0055] In some embodiments of the present invention, in step 2, before mixing solution B with solution A, the step further includes stirring solution B at 75° C. and at a speed of 400 to 600 r / min for 3 to 5 hours.

[0056] The purpose of stirring solution B for a certain period of time in the above temperature range is to ensure that the components in the solution are evenly dispersed and fully dissolved, avoid particle agglomeration, and ensure the uniformity and stability of the membrane. During the stirring process, controlling the temperature and time helps to optimize the mechanical properties, conductivity and separation efficiency of the membrane, while promoting uniform reaction and ensuring the final quality and performance of the membrane.

[0057] In some embodiments of the present invention, in step 2, the volume ratio of the solution A to the solution B is 1:1.

[0058] In some embodiments of the present invention, in step 3, the soaking is specifically: vertical soaking for 8 to 12 hours; the drying parameters are set to: drying at 80 to 120° C. for 15 to 30 minutes.

[0059] The purpose of vertical immersion is to ensure that the membrane material is in full contact with the solution, thereby forming a uniform membrane layer and optimizing its structure and performance. Immersion time beyond the above parameter range will lead to excessive adsorption or deposition on the membrane surface, resulting in uneven membrane layer, inconsistent thickness, and even affecting the mechanical strength and separation effect of the membrane. At the same time, changes in solution composition will also lead to adverse changes in the chemical structure of the membrane, thereby affecting its functionality.

[0060] In the present invention, the drying parameter settings are adjusted based on the material properties of the membrane. Different membrane materials have different sensitivities to temperature and time. Reasonable drying conditions help optimize the microstructure of the membrane and improve its mechanical strength, porosity and separation performance. In addition, the above-mentioned specific drying parameters (temperature and time) can avoid embrittlement, structural collapse or uneven pore size distribution of the membrane during the drying process, ensuring the stability and functionality of the membrane.

[0061] The second aspect of the present invention provides a polyaniline modified composite membrane prepared according to the above preparation method.

[0062] The third aspect of the present invention provides the use of the above-mentioned polyaniline modified composite membrane in oil-water separation.

[0063] The polyaniline modified composite membrane of the invention can effectively filter transformer floating oil aqueous solution, is suitable for various types of oil-water mixtures, and has good adaptability.

[0064] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0065] The pore size of the polyvinylidene fluoride (PVDF) substrate used in the embodiments of the present invention is in the range of 0.1 to 0.5 μm; commercially available polyvinylidene fluoride (PVDF) substrates with a pore size of 0.1 to 0.5 μm are suitable for the present invention.

[0066] The SiO used in the embodiments of the present invention 2 The average particle size of the powder is 25 nm.

[0067] The test method involved in the embodiment of the present invention is as follows:

[0068] Micromorphology analysis

[0069] The effect of polyaniline on the roughness of the film was studied to explore its effect on the wettability of the film. The effect of polyaniline on the roughness of the film was analyzed by scanning electron microscopy and atomic force microscopy. The microscopic morphology of different materials was observed using a field emission scanning electron microscope. The prepared sample was gold-sprayed at a voltage of 10 kV and a gold-spraying time of 90 s. The acceleration voltage in the test was 5 kV.

[0070] Surface chemical composition analysis

[0071] The chemical composition of PVDF membranes before and after PANI modification was studied by ATR-FTIR and XPS measurement methods. The functional groups in the samples were analyzed by Fourier transform infrared spectrometer. The samples to be tested were dried and the scanning range was 500-4000cm -1 .

[0072] The solid surface analysis of the samples, including the chemical composition of the fiber membrane surface, was performed using an X-ray photoelectron spectrometer with an energy analysis range of 0 to 1500 eV to cover the binding energies of all possible elemental electrons.

[0073] The phase structure was analyzed using an X-ray diffractometer with a test range of 5 to 80° and a scanning rate of 5° / min.

[0074] Mechanical properties analysis

[0075] The samples were cut into rectangular films of a certain area, and the clamping distance was set to 2 cm. The breaking strength, Young's modulus and breaking growth rate of each sample were tested using a texture analyzer, and each test was measured three times in parallel to take the average value.

[0076] Separation efficiency calculation formula

[0077] The oil content in the original solution and the filtrate was determined by infrared spectrophotometry, and the separation efficiency R (%) of the prepared membrane was calculated as shown in formula (1):

[0078]

[0079] Among them, C 0 and C 1 Represent the oil content in the original emulsion and the filtrate after filtration, respectively.

[0080] Membrane flux J(Lm -2 h -1 ), the calculation equation is as follows:

[0081]

[0082] Where V represents the volume of the filtrate (L), A (m 2 ) represents the effective area of ​​the membrane, and T represents the separation time (h).

[0083] The TOC content was tested by a total organic carbon analyzer and determined according to the non-dispersive infrared absorption method.

[0084] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0085] The present invention provides a method for preparing a polyaniline (PANI) modified composite film, the steps of which are as follows:

[0086] S1. Activate the polyvinylidene fluoride (PVDF) substrate for 0.5 to 3 hours;

[0087] S2. SiO 2 The powder was dispersed in 50 mL of polar organic solution and stirred for 1 to 3 h, which was recorded as solution A. 2 The concentration is 2-10 g / L;

[0088] S3. Dissolve PANI and polyvinylpyrrolidone (PVP) in 50 mL of an acidic solution, referred to as solution B; the concentration of PANI in solution B is 5 to 15 g / L, and the concentration of PVP is 2 to 10 g / L;

[0089] S4. The activated PVDF substrate was washed with deionized water and immersed in solution A, stirred at a temperature of 35 to 75 ° C, the stirring time was 1 to 3h, the speed was 400 to 600r / min, and the PVDF substrate was removed after stirring and washed again with deionized water;

[0090] S5. Place solution B in a constant temperature water bath at 75°C and stir for 3 to 5 hours at a speed of 400 to 600 r / min;

[0091] S6. The solution A after stirring in step S4 and the solution B after stirring in step S5 are mixed in a volume ratio of 1:1, and the mixed solution is filtered and precipitated. After that, the PVDF substrate cleaned in step S4 is vertically placed in the filtered mixed solution and soaked for 8 to 12 hours;

[0092] S7. Take out the soaked PVDF substrate and place it in a drying oven for drying at a temperature of 80 to 120° C. for 15 to 30 min to obtain a PANI-modified composite membrane, which is referred to as PANI@PVDF.

[0093] Example 1

[0094] A PANI modified composite membrane, denoted as PANI@PVDF-1, is prepared by the following steps:

[0095] S1. Activate the PVDF substrate in anhydrous ethanol for 2 hours;

[0096] S2. SiO 2 The powder was dispersed in 50 mL of dimethylformamide (DMF) solution and stirred for 2 h, which was recorded as solution A. 2 The concentration is 2g / L;

[0097] S3. Dissolve PANI and PVP in 50 mL of 1 mol·L -1 The concentration of PANI in solution B is 10 g / L, and the concentration of PVP is 2 g / L.

[0098] S4. The PVDF substrate activated in step S1 was washed with deionized water and immersed in solution A, stirred at a temperature of 75 ° C, the stirring time was 2h, the speed was 500r / min, and the PVDF substrate was removed after stirring and washed again with deionized water;

[0099] S5. Place solution B in a constant temperature water bath at 75°C and stir for 4 h at a speed of 500 r / min;

[0100] S6. The solution A after stirring in step S4 and the solution B after stirring in step S5 were mixed in a volume ratio of 1:1, and the mixed solution was filtered and precipitated, after which the PVDF substrate cleaned in step S4 was vertically placed in the filtered mixed solution and soaked for 10 hours;

[0101] S7. Take out the soaked PVDF substrate and place it in a drying oven for drying at a temperature of 100° C. for 20 min to obtain a PANI@PVDF-1 composite membrane.

[0102] The test showed that the PANI@PVDF-1 composite membrane prepared in this embodiment had a breaking strength of 30.1 MPa, a Young's modulus of 2.4 MPa, a breaking elongation of 29.8%, and a membrane flux of 441.50 Lm -2 h -1 , the floating oil / water solution separation efficiency reaches 98.5%.

[0103] Example 2

[0104] A PANI modified composite membrane, denoted as PANI@PVDF-2, is prepared by the following steps:

[0105] S1. Activate the PVDF substrate in anhydrous ethanol for 2 hours;

[0106] S2. SiO 2 The powder was dispersed in 50 mL of DMF solution and stirred for 2 h, which was recorded as solution A. 2 The concentration is 6g / L;

[0107] S3. Dissolve polyaniline and PVP in 50 mL, 1 mol·L -1 The concentration of PANI in solution B is 10 g / L, and the concentration of PVP is 6 g / L.

[0108] S4. The PVDF substrate activated in step S1 was washed with deionized water and immersed in solution A, stirred at a temperature of 75 ° C, the stirring time was 2h, the speed was 500r / min, and the PVDF substrate was removed after stirring and washed again with deionized water;

[0109] S5. Place solution B in a constant temperature water bath at 75°C and stir for 4 h at a speed of 500 r / min;

[0110] S6. The solution A after stirring in step S4 and the solution B after stirring in step S5 were mixed in a volume ratio of 1:1, and the mixed solution was filtered and precipitated, after which the PVDF substrate cleaned in step S4 was vertically placed in the filtered mixed solution and soaked for 10 hours;

[0111] S7. Take out the soaked PVDF substrate and place it in a drying oven for drying at a temperature of 100° C. for 20 min to obtain a PANI@PVDF-2 composite membrane.

[0112] The test showed that the PANI@PVDF-2 composite membrane prepared in this embodiment had a breaking strength of 55.2 MPa, a Young's modulus of 3.3 MPa, a breaking elongation of 23.5%, and a membrane flux of 475.46 Lm -2 h -1 , the floating oil / water solution separation efficiency is 90%.

[0113] Example 3

[0114] A PANI modified composite membrane, denoted as PANI@PVDF-3, is prepared by the following steps:

[0115] S1. Activate the PVDF substrate in anhydrous ethanol for 2 hours;

[0116] S2. SiO 2 The powder was dispersed in 50 mL of DMF solution and stirred for 2 h, which was recorded as solution A. 2 The concentration is 10g / L;

[0117] S3. Dissolve polyaniline and PVP in 1 mol·L -1 The concentration of PANI in solution B is 10 g / L, and the concentration of PVP is 10 g / L.

[0118] S4. The PVDF substrate activated in step S1 was washed with deionized water and immersed in solution A, stirred at a temperature of 75 ° C, the stirring time was 2h, the speed was 500r / min, and the PVDF substrate was removed after stirring and washed again with deionized water;

[0119] S5. Place solution B in a constant temperature water bath at 75°C and stir for 4 h at a speed of 500 r / min;

[0120] S6. The solution A after stirring in step S4 and the solution B after stirring in step S5 were mixed in a volume ratio of 1:1, and the mixed solution was filtered and precipitated, after which the PVDF substrate cleaned in step S4 was vertically placed in the filtered mixed solution and soaked for 10 hours;

[0121] S7. Take out the soaked PVDF substrate and place it in a drying oven for drying at a temperature of 100° C. for 20 min to obtain a PANI@PVDF-3 composite membrane.

[0122] After testing, the PANI@PVDF-3 composite membrane prepared in this embodiment has a breaking strength of 60.9 MPa, a Young's modulus of 3.1 MPa, a breaking elongation of 19.9%, and a membrane flux of 458.48 Lm -2 h -1 The separation efficiency of floating oil / water solution is 98.73%, which is the most thorough separation. The optical photograph of the PANI@PVDF-3 composite membrane prepared in this example is shown in FIG. Figure 1 As shown, FESEM images are Figure 2 As shown by Figure 2 It can be seen that compared with the unmodified PVDF membrane, the PANI@PVDF-3 composite membrane has a rougher surface and a denser structure, indicating that the polymerization of polyaniline increases the roughness of the fiber and that PANI and PVDF have good compatibility. Figure 2 It can be seen that the PANI@PVDF-3 membrane has a dense porous structure, and this compact structure gives it better mechanical properties.

[0123] The surface roughness of the film was analyzed using an atomic force microscope (AFM). Figure 3 As shown, the surface of the base film exhibits a uniform concave-convex structure due to the uniform membrane pores. However, the surface of PANI@PVDF exhibits an uneven distribution of concave-convex structures due to the different adsorption and aggregation degrees of polyaniline nanofibers in different places. The surface roughness of the PVDF membrane and the PANI@PVDF-3 composite membrane was accurately measured using an atomic force microscope. The average roughness of the PVDF membrane was 8.9nm, indicating that its surface was relatively smooth. In contrast, the average roughness of the PANI@PVDF composite membrane increased significantly to 95.39nm, which was related to the adsorption and aggregation of polyaniline nanowires on the membrane surface.

[0124] The PANI@PVDF-3 composite membrane was used to carry out multiple oil-water separation cycle tests, such as Figure 6 The total organic carbon content of the filtrate was detected to be 17.2 mg / L, which met the national wastewater discharge standard, indicating that the PANI@PVDF-3 composite membrane prepared by the present invention has good anti-fouling and reusability.

[0125] The test method for the oil-water separation cycle test is as follows:

[0126] 1. Experimental Setup

[0127] Membrane materials: Five different PANI@PVDF composite membranes were used, among which PANI@PVDF-3 composite membrane was the best choice with the best separation effect.

[0128] Filtration device: The membrane is fixed at an inner diameter of 5 cm and the effective separation area is 19.63 cm 2 The oil-water separation device used in the experiment is shown in the figure ( Figure 4 ).

[0129] 2. Preparation of Oil / Water Solution

[0130] Mix deionized water with organic solvent (transformer oil) in a ratio of V 去离子水 / V 有机溶剂 = 100 / 1. After mixing, pour into the upper glass tube to separate oil and water.

[0131] The mixed solution was filtered under a pressure of 0.07 MPa to obtain an original solution containing an oil-water mixture and a filtrate.

[0132] 3. Separation process and data recording

[0133] After each filtration, the oil content in the original solution and the filtrate was determined by infrared spectrophotometry and used to calculate the separation efficiency R (%).

[0134] The membrane flux (J) was determined by calculating the volume of the filtrate (V), the effective area of ​​the membrane (A), and the separation time (T).

[0135] 4. Cycle test steps

[0136] In each cycle experiment, the PANI@PVDF-3 composite membrane was briefly rinsed with water to restore the membrane flux.

[0137] The experiment was repeated several times, and the membrane flux and TOC content were checked after each experiment.

[0138] TOC analysis: The TOC content in the filtrate is tested by a total organic carbon analyzer using the non-dispersive infrared absorption method to evaluate the durability of the oil-water separation effect.

[0139] 5. Cycle Experiment Results

[0140] After 5 cycles, the membrane flux decreased slightly, but it could be restored to close to the original value by simple rinsing.

[0141] After the fifth cycle, the TOC content in the filtrate was 17.2 mg / L, which met the national wastewater discharge standards.

[0142] The experimental results show that the PANI@PVDF-3 composite membrane has good anti-fouling and reusability, is suitable for multiple uses and can maintain a good separation effect.

[0143] 6. Summary

[0144] The cycle test can evaluate the performance of the composite membrane after multiple uses. The flux of the membrane decreases slightly after multiple filtrations, but can be restored by simple rinsing. The TOC content meets environmental protection standards, proving that the membrane has good anti-fouling and reusability.

[0145] Example 4

[0146] The only difference from Example 3 is that in step S4, stirring is performed at a temperature of 35° C., and the remaining steps and parameters are the same as those in Example 3; the obtained PANI modified composite membrane is denoted as PANI@PVDF-4.

[0147] After testing, the membrane flux of the PANI@PVDF-4 composite membrane prepared in this example is 339.62Lm -2 h -1 , the floating oil / water solution separation efficiency is 95.5%.

[0148] Example 5

[0149] The only difference from Example 3 is that in step S4, stirring is performed at a temperature of 55° C., and the remaining steps and parameters are the same as those in Example 3; the obtained PANI modified composite membrane is denoted as PANI@PVDF-5.

[0150] After testing, the membrane flux of the PANI@PVDF-5 composite membrane prepared in this example is 407.54Lm -2 h -1 , the floating oil / water solution separation efficiency is 98.5%.

[0151] Figure 5 The results of the test of separating floating oil / water solution using five PANI@PVDF composite membranes prepared in Examples 1 to 5 of the present invention; in the figure, bottles ABCD correspond to PANI@PVDF-2 composite membrane, PANI@PVDF-4 composite membrane, PANI@PVDF-1 composite membrane and PANI@PVDF-5 composite membrane respectively, and bottle E uses PANI@PVDF-3 composite membrane. Figure 5 It can be seen that the oil content gradually decreases after separation. Bottle A has obvious oil droplets, indicating that the oil-water separation is incomplete. Bottles B, C and D have a small amount of oil droplets, indicating that the oil-water separation is incomplete. Bottle E has almost no visible oil droplets, and the oil-water separation is basically complete. Bottle E is the oil-water separation of PANI@PVDF-3 composite membrane, indicating that when the heating temperature is 75°C and SiO 2When the concentration ratio of PVP to polyaniline is 1:1:1, the membrane separation effect is the best. The membrane flux of the original membrane is 390.5L m -2 h -1 , separation efficiency 53.2%.

[0152] It was also verified that the stirring temperature in step S4 was further increased to 80°C, 85°C, and 90°C on the basis of Example 3 (that is, the only difference from Example 3 is that in step S4, stirring is performed at 80°C, 85°C, and 90°C, respectively, and the remaining steps and parameters are the same as those in Example 3). The results show that as the stirring temperature in step S4 is gradually increased from 35°C to 90°C, the flux of the membrane is initially increased, because high temperature helps to increase the fluidity of the solution and reduce the resistance of the membrane, thereby accelerating the separation process. However, excessively high temperatures will cause changes in the structure of the membrane, especially the pore structure of the membrane will be deformed due to thermal expansion or contraction, thereby affecting the mechanical strength and stability of the membrane. High temperatures will also cause the surface coating or modified materials of the membrane (such as SiO 2 and polyaniline) will degrade or fall off, which will affect the hydrophilicity and wettability of the membrane, resulting in a decrease in separation efficiency. In addition, long-term stirring at too high a temperature will reduce the durability of the membrane, reduce the membrane's ability to be reused, and make the membrane surface more susceptible to contamination, affecting its cleaning effect. Therefore, the temperature should be kept within a suitable range to ensure long-term stability of the membrane and optimal separation effect.

[0153] Comparative Example 1

[0154] A PANI modified composite membrane, denoted as PANI@PVDF-D1, is prepared by the following steps:

[0155] S1. Activate the PVDF substrate in anhydrous ethanol for 2 hours;

[0156] S2. SiO 2 The powder was dispersed in 50 mL of DMF solution and stirred for 2 h, which was recorded as solution A. 2 The concentration is 10g / L;

[0157] S3. Dissolve polyaniline and PVP in 50 mL, 1 mol·L -1 The concentration of PANI in solution B is 10 g / L, and the concentration of PVP is 10 g / L.

[0158] S4. The solution A was stirred at a temperature of 75°C for 2 h at a speed of 500 r / min;

[0159] S5. Place solution B in a constant temperature water bath at 75°C and stir for 4 h at a speed of 500 r / min;

[0160] S6. The solution A after stirring in step S4 and the solution B after stirring in step S5 were mixed in a volume ratio of 1:1, and the mixed solution was filtered and precipitated. After that, the PVDF substrate activated in step S1 was washed with deionized water and placed vertically in the filtered mixed solution for 10 hours;

[0161] S7. Take out the soaked PVDF substrate and place it in a drying oven for drying at a temperature of 100°C for 20 minutes to obtain a PANI@PVDF-D1 composite membrane. (That is, the only difference from Example 3 is that the step of immersing the PVDF substrate in solution A is omitted)

[0162] The PANI@PVDF-D1 prepared in this comparative example was subjected to the same effect verification as in Example 3. The results showed that the breaking strength of PANI@PVDF-D1 was 40.3 MPa, Young's modulus was 2.0 MPa, the breaking elongation was 28.7%, and the membrane flux was 382.5 Lm -2 h -1 , floating oil / water solution separation efficiency: 83%.

[0163] Comparing Comparative Example 1 and Example 3, it can be seen that omitting the step of immersing the PVDF substrate in Solution A will significantly reduce the performance of the composite membrane. Specifically, the mechanical properties deteriorate, such as the reduction of fracture strength and Young's modulus, and the hydrophilicity and wettability decrease due to insufficient surface roughness, which in turn leads to a significantly lower separation efficiency and membrane flux than Example 3. At the same time, due to the lack of SiO on the membrane surface, 2 Due to the modification of the coating, the filtrate after oil-water separation has a high oil content and is difficult to meet environmental emission standards.

[0164] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a polyaniline modified composite film, characterized in that: The following steps are involved: Step 1, activating and cleaning the polyvinylidene fluoride sheet, and then immersing it in solution A and stirring it. After the stirring is completed, the polyvinylidene fluoride sheet is taken out and cleaned to obtain a treated polyvinylidene fluoride sheet; Step 2, mixing the solution A and the solution B and filtering them to obtain a mixed solution; Step 3, soaking the treated polyvinylidene fluoride sheet in the mixed solution, taking it out and drying it after soaking, to obtain the polyaniline modified composite film; The solution A is a SiO2 solution; The solution B is a mixed solution of polyaniline and polyvinyl pyrrolidone.

2. The method for preparing a polyaniline modified composite membrane according to claim 1, characterized in that: The polyvinylidene fluoride substrate is placed in anhydrous ethanol for activation; the activation time is 0.5 to 3 hours.

3. The method for preparing a polyaniline modified composite membrane according to claim 1, characterized in that: The concentration of SiO2 in the solution A is 2-10 g / L; the solvent of the solution A is dimethylformamide; the particle size of SiO2 in the solution A is 5 nm-50 nm.

4. The method for preparing a polyaniline modified composite membrane according to claim 1, characterized in that: The concentration of polyaniline in the solution B is 5-15 g / L, the concentration of polyvinyl pyrrolidone is 2-10 g / L; the solvent of the solution B is 0.5-1.5 mol·L -1 of hydrochloric acid solution.

5. The method for preparing a polyaniline modified composite membrane according to claim 1, characterized in that: In step 1, the stirring parameters are set as: stirring at a temperature of 35 to 75° C. and a speed of 400 to 600 r / min for 1 to 3 hours.

6. The method for preparing a polyaniline modified composite membrane according to claim 1, characterized in that: In step 2, before mixing solution B with solution A, the method further includes stirring solution B at 75° C. and at a speed of 400 to 600 r / min for 3 to 5 hours.

7. The method for preparing a polyaniline modified composite membrane according to claim 1, characterized in that: In step 2, the volume ratio of the solution A to the solution B is 1:

1.

8. The method for preparing a polyaniline modified composite membrane according to claim 1, characterized in that: In step 3, the soaking is specifically: vertical soaking for 8 to 12 hours; the drying parameters are set as: drying at 80 to 120° C. for 15 to 30 minutes.

9. The polyaniline modified composite membrane prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the polyaniline modified composite membrane as claimed in claim 9 in oil-water separation.

Citation Information

Patent Citations

  • Preparation method of polyaniline nano composite film

    CN102068925A

  • Preparation method of polyaniline hollow fiber forward osmotic membrane

    CN109621753A

  • Preparation method of high-performance MABR hollow fiber composite membrane

    CN113368711A

  • Method for preparing high-performance reverse osmosis membrane by using silicon dioxide / polyaniline nanoparticle modified base membrane

    CN117101442A

  • Membrane compositions and methods for making and using them

    US20110240556A1